设随机变量X服从正态分布N(3,16) [br][/br] 则Y=(X-3)/4服从( )
A: N(3,4)
B: N(0,1)
C: N(0,16)
D: N(3,16)
A: N(3,4)
B: N(0,1)
C: N(0,16)
D: N(3,16)
举一反三
- 设随机变量(X,Y)~N(1, 2; 3, 4; 0), 则2X-Y服从的分布为 A: N(0,2) B: N(0,10) C: N(0,16) D: N(0.8)
- 设随机变量(X,Y)~N(1, 2; 3, 4; 0), 则2X-Y服从的分布为 A: N(0,2) B: N(0,10) C: N(0,16) D: N(0.8)
- 设随机变量X 服从标准正态分布N(0, 1), 则Y = 2X – 1服从( ) A: N(0,1) B: N(-1,4) C: N(-1, 1) D: N(-1, 3)
- 设随机变量X~N(1, 1),则Y=2X+1服从()分布 A: N(3, 3) B: N(3, 4) C: N(3, 5) D: N(1, 3)
- 设随机变量X服从N(1,4),Y=2X+1,则Y所服从的分布为( ). A: N(3,4) B: N(3,8) C: N(3,16) D: N(3,17)